1997
DOI: 10.1302/0301-620x.79b5.0790719
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Treatment of Developmental Dysplasia of the Hip With the Pavlik Harness

Abstract: We report the six-year results of a prospective, controlled demographic trial of developmental dysplasia of the hip (DDH) treated in the Pavlik harness using ultrasound supervision. Our aim was to assess the value of ultrasound and its role in monitoring reduction in the harness, in terms of progression or failure of reduction at an early state. We conclude that ultrasound monitoring has led to an acceptably low level of intervention, a high reduction rate and minimal iatrogenic complications. The trial is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 16 publications
1
24
3
Order By: Relevance
“…Our data indicated that the success rate was 84 % and this rate was lower than that reported by (Taylor et al, 1997) as they got 95.7% successful reduction with Pavlik harness in their cases. Similar results was reached by (Grill et al, 1988) as they got 95.35% healing rate in infant with dysplastic hips but they observed Avascular necrosis of the femoral head in 2.38% of their cases.…”
Section: Resultscontrasting
confidence: 73%
“…Our data indicated that the success rate was 84 % and this rate was lower than that reported by (Taylor et al, 1997) as they got 95.7% successful reduction with Pavlik harness in their cases. Similar results was reached by (Grill et al, 1988) as they got 95.35% healing rate in infant with dysplastic hips but they observed Avascular necrosis of the femoral head in 2.38% of their cases.…”
Section: Resultscontrasting
confidence: 73%
“…The initial ultrasound assessment showed 65.8% to be displaced and 17.9% to be dislocated. They report that 16 hips (4.3%) failed to reduce, requiring further treatment, 7 hips (3.2%) showed continued dysplasia at 5 years and 0.3% had mild avascular necrosis [12]. The use of ultrasound during splintage also allows the monitoring of the adequacy of treatment, identifying failure early in order to allow a change in management [13].…”
Section: Introductionmentioning
confidence: 99%
“…After initial clinical assessment, patients treated in this way were reviewed weekly using a static ultrasound [16].…”
Section: Methodsmentioning
confidence: 99%